Imperium teatralne Maxa Reinhardta - Małgorzata Leyko (Pamiętnik Teatralny, 2018)
Max Reinhardt, a director who had an enormous influence on the style and convention of European theatre in the 20th century, can also be credited with creating a modern model of theatre enterprise; he ran several theatres at the same time, and the gusto with which he ruled his theatre empire earned him the name of der Theatrarch in the German-speaking community. Reinhardt’s actions as manager of Berlin theatres—the Deutshes Theater, the Kammerspiele, and the Grosses Schauspielhaus—is presented against the backdrop of the German theatre management system that had been in place since 1896, when Gewerbefreiheit, the freedom of trade law that made theatre enterprise no different from any other commercial endeavour came into effect. In a sense, the law spoiled the theatre whose mission had hitherto been to raise the culture of German society, and as a result, the number of theatres offering popular entertainment increased dramatically. Faced with strong competition, Reinhardt was nevertheless able to run several theatres without lowering high artistic standards and still turn a profit.